Analisis Timbulan Lumpur dan Kualitas Lumpur Hasil Proses Pengolahan Air Bersih di WTP Kampus IPB Dramaga Bogor - Elissa, Anastasia; Saptomo, Satyanto Krido (Jurnal Teknik Sipil dan Lingkungan, 2020)
IPB University Dramaga has three units of WTP, two units at WTP Ciapus and one unit at WTP Cihideung. WTP produce sludge from alum coagulant and were disposed directly into water bodies. The purpose of this study were to identify the volume and characteristics of the sludge generation, comparing the sludge quality with regulations, and provide alternative recommendations for sludge management. Sludge samples were taken from effluent of clarifier and filtration. The sludge generated in the WTP Ciapus 1 was 18.63 kg/day while in the WTP Cihideung was 85.51 kg/day. The characteristics of the sludge produced were liquid and inorganic. The sludge pH of some samples in WTP Ciapus did not met the quality standards. Temperature, concentration of COD, iron (Fe), and aluminum (Al) fulfilled the quality standards. The sludge from WTP IPB Campus can be processed by collecting and drying. Dried sludge can be used as compost and the backwash residue can be recycled.